STRENGTHENING THE INNOVATION ECOSYSTEM IN SURAKARTA: ANALYSIS OF BARRIERS AND PRACTICAL RECOMMENDATIONS - Fery Indra Kurniawan; Farid Adi Prasetya (Universitas Muhammadiyah Surakarta, 2025)
The City of Surakarta holds significant potential for innovation development; however, its growth has thus far been hindered by the lack of optimal engagement from various stakeholders, such as local government agencies, academia, and the private sector. The background of this study is to identify the factors that obstruct innovation growth and to formulate strategies that can improve the city's innovation score. The objective of this research is to develop policy recommendations that can strengthen the innovation ecosystem, as well as to draft a comprehensive roadmap to guide the effective implementation of innovation initiatives. The analysis shows that suboptimal engagement, lack of coordination among stakeholders, and limited capacity in human resources and technological infrastructure are the main challenges. The conclusion of this study emphasizes the importance of building a structured collaboration platform, developing human resource capacity, and preparing a clear innovation roadmap to achieve sustainable innovative growth. The implications of these recommendations include the need for adequate budget allocation, strengthened coordination among stakeholders, and intensive training to enhance skills in technology and innovation management. The novelty of this research lies in the integration of cross-sector collaboration strategies with technology and human capacity development into a holistic approach, along with the emphasis on active community participation in the innovation process. By implementing these recommendations, it is expected that the City of Surakarta can create an inclusive and sustainable innovation environment, which will ultimately support local economic growth and the achievement of the Sustainable Development Goals (SDGs).